Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Camat Kampar - Syafrina, Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This research was conducted at the Kampar District Office. The purpose of this study was to determine the influence of the work environment and organizational culture on the performance of employees of the Kampar District Office. The population in this study were all employees who worked at the Kampar sub-district office, namely 32 people. In this study, sampling used a saturated sample, so the sample used in this study was 32 people. The data used are primary and secondary data with analysis using multiple linear regression. The results showed that the work environment and organizational culture had a positive relationship to the performance of Kampar sub-district office employees. This can be seen in the multiple linear regression equation, namely Y = 9.324+0.541X1+0.451X2. And the results of the t test and F test showed that all independent variables had a significant effect on the dependent variable, and the magnitude of the independent variable's influence on the dependent variable was 61.7 percent while the remaining 38.3 percent was influenced by other factors not included in the study, for example factors of discipline, compensation, and leadership and others.